Quality and safety of food as a component - Yudicheva, O.; Kalashnyk, O.; Moroz, S.; Kalian, O. (Nemoros s.r.o., 2019)
Extra oat flakes, «Hercules Power» produced by Ltd. «Hercules and K», according to organoleptic parameters, correspond to the requirements of GOST 21149. Consequently, the analysis of the results of the research of the content of toxic elements in the oat flakes of extra production by Ltd. «Hercules and K» showed that this food product meets the requirements of GOST 21149-93 and SanPiN 2.3.2.560-96 according to measured safety parameters
Keywords: organoleptic method; oat flakes; toxic elements; quality; safety of food; вівсяні пластівці; органолептичний метод; токсичні елементи; якість; безпечність продуктів харчування